2007
DOI: 10.2172/926968
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term US Industrial Energy Use and CO2 Emissions

Abstract: We present a description and scenario results from our recently-developed long-term model of United States industrial sector energy consumption, which we have incorporated as a module within the O bj ECTS-MiniCAM integrated assessment model. This new industrial model focuses on energy technology and fuel choices over a 100 year period and allows examination of the industrial sector response to climate policies within a global modeling framework. A key challenge was to define a level of aggregation that would b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…4) Alteration of product design and waste protocols to facilitate reuse and recycling. The long term US industrial energy use and CO 2 emissions have been reported by Wise et al [4]. The authors studied the energy technologies and fuel choices over a 100-year period and the response of the industrial sector to climate policies.…”
Section: Co 2 Emissions Due To Energy Use In Industrymentioning
confidence: 93%
“…4) Alteration of product design and waste protocols to facilitate reuse and recycling. The long term US industrial energy use and CO 2 emissions have been reported by Wise et al [4]. The authors studied the energy technologies and fuel choices over a 100-year period and the response of the industrial sector to climate policies.…”
Section: Co 2 Emissions Due To Energy Use In Industrymentioning
confidence: 93%
“…Industrial energy use and CO 2 emissions in the United States (US) have been reported (Wise et al, 2007). The authors used appropriate models to predict fuel choices and energy technology use on a long term under policy constraints.…”
Section: Energy Use and Co 2 Emissions In Industrymentioning
confidence: 99%
“…The U.S. industrial module, detailed in Wise et al (2006), disaggregates the sector into 12 industry groups (nine manufacturing and three non-manufacturing). The designation of the 12 industry groups was informed by patterns of service demands and fuel consumption in the Manufacturing Energy Consumption Survey (MECS; EIA 1999).…”
Section: Industrymentioning
confidence: 99%